Darfour : triste anniversaire - Alice Franck; Ivan Deret (EchoGéo)
The Darfur crisis entered its sixth year. At First almost ignored, it benefits today from a large coverage by Medias, and even became of source of disputes. However, apart of the relief aid provided to persons, the international community remains unable to find a solution to a lasting and more and more complicated crisis.